RETRACTED: Households’ Perception and Environmentally Friendly Technology Adoption: Implications for Energy Efficiency - Fatima, Nousheen; Li, Yanbin; Li, Xiaoyu; Abbas, Wajid; Jabeen, Gul; Zahra, Taskeen; Işık, Cem; Ahmed, Naseer; Ahmad, Munir; Yasir, Ammar (Frontiers in Energy Research, 2022)
Since employing environmentally friendly technologies (EFTs) is a complicated and difficult process that is affected by multiple factors, researchers are encouraged to explore those influence factors. This research aims to estimate the households’ perception factors affecting the adoption intentions of EFTs. Based on a questionnaire survey from 782 Pakistani households, a structural equation modeling strategy yields empirical results. The main findings are: firstly, the drivers of adoption intention of EFTs include technological awareness, perceived environmental importance, perceived behavioral control, and perceived benefits. Secondly, significant barriers to the adoption intention of EFTs involve the perceived cost of EFTs and the perceived risk-averse behavior of households. Thirdly, among all factors, perceived environmental importance reveals the most substantial contribution, whereas perceived risk-averse behavior shows the least contribution to the adoption intention of EFTs. Finally, given these results, strengthening the financial benefits, controlling the roaring cost of EFTs, and the provision of rebates and subsidization are suggested to upscale the adoption intention of EFTs by the households.